Critical thinking attitudes for reasoning with points of view - Panayiotou, Christiana; Bennett, Brandon (My University, 2009)
This paper provides the semantics and axiomatization of propositional attitudes relevant to the critical thinking activity. This axiomatization can be used to provide a common ground for reasoning with different resources for the purpose of representing and analysing their points of view about particular issues. It can also be used during interaction with other (possibly human) agents in order to model their mental states and plan argumentative disourse. © 2009 IEEE.
Keywords: Cognitive systems; Learning systems; Learning systems